Communicative Language Teaching: Improving EFL Students’ Speaking Skills in an Indonesian Islamic Boarding School Context - Selamat Husni Hasibuan; Heridayani; Imelda Darmayanti Manurung, (Journal of Communication in Scientific Inquiry (JCSI), 2024)
This study examines the effect of the Communicative Language Teaching (CLT) approach on English foreign language students’ speaking skills at an Indonesian Islamic boarding school. This study is framed within a quasi-experimental design using a pre-test and post-test for both groups to answer the main research question. The participants were 80 students from two classes, one class was recruited to participate as the experimental group, and the other was the control group. The experimental group was taught using CLT activities such as interviewing, role-playing, discussion, games, and problem-solving, while the control group was taught using the traditional approach. The research finding indicated that the experimental group achieved higher scores than the control group. This finding implied that students who were taught using the CLT approach got better speaking achievement than those taught conventionally. Ultimately, this study offers practical suggestions for pedagogy.